Empirical Study on the Development of Student Religiosity from Teacher and Student Perspectives. - Fitrah Ainul Mawaddah; Rahmat Aziz; M. Samsul Hadi; Muhammad Adip Fanani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Religiosity is religious appreciation that is expressed through daily worship, namely praying and reading holy books. Religious personal characteristics are reflected in complete faith, diligent practice of worship and noble morals (faith, Islam and ihsan). This research aims to describe and analyze the perspectives of teachers and students in developing student religiosity at school. This research uses a qualitative approach through observation and interviews. The subjects of this research were teachers and students from two junior high schools. The number of teachers interviewed was 6 people and 12 students who provided information about the strategies used by teachers in developing religiosity. The quantitative data was obtained from the results of distributing questionnaires to 255 students whose level of religiosity was measured. The results of the research show that religiosity has been implemented well and consistently at Madrasah Tsanawiyah Al-Ma'arif 01 Singosari and SMP Islam Al-Ma'arif Singosari, activities carried out include: Al-Qur'an literacy, Yasinan, Reading Sholawat, Reading Asmaul Husna, Reading Tahlil Istighosah, midday prayer in congregation, Dhuha prayer in congregation and singing national songs. The implementation methods are example, habituation and advice.